Oxford Learner's Spanish Dictionary - Editors Castillo, Ximens [et al.] (Oxford, New York Oxford University Press, 2006)
This comprehensive dictionary fulfills the requirements of the KS3 Modern Languages Framework from KS3 to GCSE. It includes example sentences to illustrate how the language works and to meet sentence building requirements, Spanish verb tables and boxed entries for important function words, with explanations of usage
Keywords: Spanish language -- English language